Quality of life in children with infrequent congenital heart defects: Cohort study with one-year of follow-up (2020)
Background: The evidence regarding patient related outcomes in children with infrequent congenital heart defects (I-CHD) is very limited. We sought to measure quality of life (QoL) in children with I-CHD, and secondarily, to describe QoL changes after one-year of follow-up, self-reported by children and through their caregivers' perspective. Methods: We assembled a cohort of children diagnosed with an I-CHD in a cardiovascular referral center in Colombia, between August 2016 and September 2018. At baseline and at one-year follow-up, a clinical psychology assessment was performed to establish perception of QoL. The Pediatric Quality of Life Inventory (PedsQL) 4.0 scale was used in both general and cardiac modules for patients and for their caregivers. We used a Mann-Whitney U test to compare scores for general and cardiac modules between patients and caregivers, while a Wilcoxon test was used to compared patients' and caregivers' baseline and follow-up scores. Results are presented as median and interquartile range. Results: To date, QoL evaluation at one-year follow-up has been achieved in 112/157 patients (71%). Self-reported scores in general and cardiac modules were higher than the QoL perceived through their caregivers, both at baseline and after one-year of follow-up. When compared, there was no statistically significant difference in general module scores at baseline between patients (median = 74.4, IQR = 64.1-80.4) and caregivers scores (median = 68.4, IQR = 59.6-83.7), p = 0.296. On the contrary, there was a statistical difference in baseline scores in the cardiac module between patients (median = 79.6, IQR = 69.7-87.4) and caregivers (median = 73.6, IQR = 62.6-84.3), p = 0.019. At one-year of follow-up, scores for the general module between patients (median = 72.8, IQR = 59.2-85.9) and caregivers (median = 69.9, IQR = 58.1-83.7) were not statistically different (p = 0.332). Finally, a significant difference was found for cardiac module scores between patient (median = 75.0, IQR = 67.1-87.1) and caregivers (median = 73.1, IQR = 59.5-83.8), p = 0.034. Conclusions: QoL in children with I-CHD can be compromised. However, children have a better perception of their QoL when compared with their caregivers' assessments. To provide high-quality care, besides a thorough clinical evaluation, QoL directly elicited by the child should be an essential aspect in the integral management of I-CHD. © 2020 The Author(s).